The value of preoperative contrast-enhanced breast magnetic resonance imaging on surgical planning in breast cancer patients - KAYA, HANDAN; GÜLLÜOĞLU, MAHMUT BAHADIR; ÇİMŞİT, NURİ ÇAGATAY (My University, 2012)
Objective: Accurate detection of tumor stage and no recurrent tumor after surgery play a determinant role in surgical planning in breast cancer patients. Breast magnetic resonance imaging (MRI) is being increasingly used in preoperative planning for breast cancer. The aim of this study is to evaluate the incremental value of preoperative breast MRI to surgical planning in women with diagnosis of breast cancer. Patients and methods: Thirty patients were enrolled in this study. Lesions were categorized according to the Breast Imaging Reporting and Data System (BI-RADS) classification. The data were analyzed according to the benefits and detriments of MRI findings and changes in surgical planning made according to MRI results. Results: There was a high correlation between primary tumor size and breast MRI-histopathologic measurements (r:0.796, p:0.00). Fourteen additional lesions were detected in 11 patients (%36) with MRI. MRI findings were concordant with histopathologic results except in 2 patients. In 17% of total patient group, the surgical approach changed according to breast MRI findings. An additional breast-conserving surgery (BCS) was applied in 1 of 16 (%6.5) patients with synchroneus contrlateral breast cancer whom were planned to undergo mastectomy. In 4 patients (28%) with BCS decision, the surgical approach was changed to mastectomy. In one patient, the border and extansion of the primary cancer was detected more clearly by MRI and the decision of BCS was changed to mastectomy.
Keywords: Tıp; Yaşam Bilimleri; Sağlık Bilimleri; Temel Tıp Bilimleri; Biyokimya; Temel Bilimler; Medicine; Life Sciences; Health Sciences; Fundamental Medical Sciences; Biochemistry; Natural Sciences; ÜREME BİYOLOJİSİ; Biyoloji ve Biyokimya; Yaşam Bilimleri (LIFE); REPRODUCTIVE BIOLOGY; BIOLOGY & BIOCHEMISTRY; Life Sciences (LIFE); Biyokimya (tıbbi); Biochemistry (medical); Breast neoplasms; surgery; magnetic resonance imaging; staging; recurrence